Struggling in no-man’s land between childhood and adulthood – a phenomenological-hermeneutical video-observation study exploring adolescent males’ encounters with general practitioners - Johanna Haraldsson; Linus Johnsson; Per Kristiansson; Ylva Tindberg; Lena Nordgren (Scandinavian Journal of Primary Health Care)
Objective Many adolescent males report negative experiences of consultations with general practitioners (GPs), which contrasts with the importance of patient-centredness that GPs themselves emphasise. A better understanding of this discrepancy might facilitate improvements. The aim was to explore and describe adolescent males’ encounters with GPs in Swedish primary healthcare centres using a lifeworld perspective.Design Qualitative lifeworld-based study. Video-recorded observations were analysed using a phenomenological-hermeneutical method.Setting Two primary healthcare centres in mid-Sweden.Subjects Nine males aged 15 to 19, video-recorded during their encounters with GPs in March through May 2022.Findings Adolescent males navigate between being children in need of parental support and men who can take initiative and responsibility. They face cognitive, emotional, and relational demands, the complexity of which renders them particularly vulnerable. When feeling exposed and not knowing what to expect, they struggle to make themselves understood, and to understand what the GP is saying and what is happening. The difficulties that they have disclosed to the GP in trust need to be recognised and carefully acted upon. Thus the GP must respond appropriately to this complex mix of vulnerabilities to prevent feelings of disappointment or of having exposed themselves in vain.Conclusion The complexity of encounters with adolescent males imposes great demands on GPs to identify and adapt to their individual needs. A proper ethical response involves helping them navigate the challenges of the consultation while also respecting them as persons and meeting their age-dependent needs.